The earth a very short introduction - Redfern, Martin (Oxford, 2013)
Martin Redfern explores the most recent geological research, explaining how new advances in the understanding of plate tectonics, seismology, and satellite imagery have enabled us to begin to see the earth for what it is: a dynamic and ever-changing planet. This clear and fascinating book brings the story of the earth up to date, revealing our present understanding of the complex processes that govern our planet